2020
DOI: 10.47941/jep.437
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Online Past Examination Papers and Academic Performance of Information Technology Students at Jomo Kenyatta University- Eldoret Campus

Abstract: Purpose: The aim of this study was to determine the influence of utilization of online past examination papers on academic performance of IT students at Jomo Kenyatta University.Methodology: Descriptive survey research design was used in this study. Respondents were the 105 undergraduate students in Information Technology Department and 2 librarians in Jomo Kenyatta University of Agriculture and Technology-Eldoret Campus. They were sampled using stratified sampling, while Head of library and the library staff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The findings of this study agree with the findings of Sivathaasan and Velnampy (2013), who examined the use of DR and academic performance of university teachers in University of Jaffna, Sri Lanka, and revealed that usage of DR has a strong positive association with academic performance (r=0.623, p<0.01). Moreover, Kipkosgei (2020) found that there is a positive and significant relationship between ebooks, e-journals, online past examination papers and academic performance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The findings of this study agree with the findings of Sivathaasan and Velnampy (2013), who examined the use of DR and academic performance of university teachers in University of Jaffna, Sri Lanka, and revealed that usage of DR has a strong positive association with academic performance (r=0.623, p<0.01). Moreover, Kipkosgei (2020) found that there is a positive and significant relationship between ebooks, e-journals, online past examination papers and academic performance.…”
Section: Discussionmentioning
confidence: 97%
“…Academic personnel should continue to utilize the many e-resources made accessible to them, according to the report. Kipkosgei (2020) investigated the link between the use of DR and the academic achievement of Jomo Kenyatta University of Agriculture and Technology (JKUAT) undergraduate information technology students. The study employed a descriptive survey research approach.…”
Section: Literature Reviewmentioning
confidence: 99%